An Assessment of the financial viability and income impact of small scale irrigation in Ethiopia - Makombe, Godswill; Hagos, Fitsum; Namara, Regassa E.; Awulachew, Seleshi Bekele (2008)
Recently, there has been very little irrigation development in Sub-Saharan Africa. The main reasons cited for this lack of interest in developing irrigation in Sub-Saharan Africa is that irrigation projects are expensive and perform poorly compared to projects from other regions. However, when classified into success and failure projects, the Sub-Saharan Africa success projects? investment costs are not significantly higher than from other regions. African countries like Ethiopia, which has embarked on an agricultural led development program, aspire to use irrigation as a development strategy with small scale irrigation playing a key role in rural development. This study evaluates the financial performance of small scale irrigation using O & M and investment recovery, and the ability to replicate the investments. It is concluded that the systems are financially viable and provide a low cost development option for rural areas.